Subthalamic nucleus activity during stopping of rhythmic finger tapping - Fischer, P (University of Oxford, 2017)
The data was collected between 2015 and 2016 at the John Radcliffe Hospital (Oxford) and the National Hospital for Neurology and Neurosurgery (London) in 9 patients with Parkinson's disease who had undergone deep brain stimulation surgery. Patients performed a stopping task while local field potentials from the subthalamic nucleus and scalp EEG channels (C3, C4, Cz, Fz, Pz) were recorded with a TMSi Porti amplifier.